Gradual Acquisition of Professional Knowledge, Audit Quality and Audit Fees - Xu, Gaoshuang; Ding, Rui; Cheng, Hanxiu; Xing, Qiuhang (Frontiers in Psychology, 2022)
The acquisition of professional knowledge is a core issue in the formation of auditor industry expertise; however, previous literature has neglected the time required for auditors to acquire professional knowledge. We examine the audit quality and fees of audit firms in different stages of an auditor acquiring professional knowledge and find that, in the initial stage of the process of knowledge acquisition, audit quality and audit fees decrease. However, in the long run, knowledge learning has a more obvious effect on the improvement of audit quality and audit fees. Specifically, knowledge learning has a positive effect on the development of audit firms.